2016
DOI: 10.3389/fphys.2016.00626
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Activates the Jak3/STAT3 Signaling Pathway to Mediate Glucose Uptake in Skeletal Muscle Cells

Abstract: Myokines are specialized cytokines that are secreted from skeletal muscle (SKM) in response to metabolic stimuli, such as exercise. Interleukin-15 (IL-15) is a myokine with potential to reduce obesity and increase lean mass through induction of metabolic processes. It has been previously shown that IL-15 acts to increase glucose uptake in SKM cells. However, the downstream signals orchestrating the link between IL-15 signaling and glucose uptake have not been fully explored. Here we employed the mouse SKM C2C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 71 publications
(144 reference statements)
3
69
1
Order By: Relevance
“…The IL6 myokine plays a role in the beneficial effect of serum from exercised humans Table 3). We identified 2 interesting candidates that signal through STAT3: IL-6 and IL-15 (30,37,38). Serum from subjects before and after training was incubated with IL6-neutralizing antibody before being added to EndoC-bH1 cells in the presence of cytokines or thapsigargin.…”
Section: Resultsmentioning
confidence: 99%
“…The IL6 myokine plays a role in the beneficial effect of serum from exercised humans Table 3). We identified 2 interesting candidates that signal through STAT3: IL-6 and IL-15 (30,37,38). Serum from subjects before and after training was incubated with IL6-neutralizing antibody before being added to EndoC-bH1 cells in the presence of cytokines or thapsigargin.…”
Section: Resultsmentioning
confidence: 99%
“…74,89 It has been reported that the signalling pathway for IL-15, induces hypoxia-inducible factor-1 α (HIF-1α) expression via JAK3/ STAT3 activation. In C2C12 myotubes, IL-15 increases basal and insulin-stimulated glucose uptake, GLUT4 translocation and GLUT4 mRNA levels.…”
Section: Interleukin-15mentioning
confidence: 99%
“…In C2C12 myotubes, IL-15 increases basal and insulin-stimulated glucose uptake, GLUT4 translocation and GLUT4 mRNA levels. 74,89 It has been reported that the signalling pathway for IL-15, induces hypoxia-inducible factor-1 α (HIF-1α) expression via JAK3/ STAT3 activation. The activation of HIF-1α expression leads to an increase in GLUT4 translocation from the cytoplasm to the plasma membrane, accounting for the increase in glucose uptake in cultured myocytes in vitro and in isolated skeletal muscle ex vivo.…”
Section: Interleukin-15mentioning
confidence: 99%
See 2 more Smart Citations